Untargeted metabolomics reveal rhizosphere metabolites mechanisms on continuous ramie cropping - Fu, Yafen; Liu, Tongying; Wang, Xin; Wang, Yanzhou; Gong, Qiulin; Li, Guang; Lin, Qian; Zhu, Siyuan (Frontiers in Plant Science, 2023)
Ramie is an important fiber feed dual-purpose crop in China and plays an important role in the national economy. However, ramie yield and quality can be reduced after many years of continuous cultivation. Currently, relatively little research has been conducted on rhizosphere metabolites and their pathways in continuous ramie cropping. Therefore, a healthy group (CK) and obstacle groups (XZQG, JZ, DJY, and GXD) with 8 years of continuous cultivation were selected for the study. LC-MS and GC-MS untargeted metabolomics were used to explore and analyze ramie rhizosphere metabolites and pathways. The results revealed that significant differences in the agronomic traits of ramie occurred after 8 years of continuous cultivation, with dwarfed plants and decreased yields in the obstacle groups. Metabolomic analysis identified 49 and 19 rhizosphere metabolites, including lipids, organic acids, phenols, and amino acids. In addition, four differential metabolic pathways (phenylpropanoid biosynthesis, fatty acid metabolism, amino acid metabolism, and ascorbate and aldarate metabolism) were elucidated. It was also clarified that sinapic acid, jasmonic acid, glutamine, and inositol might be the main metabolites affecting ramie continuous-cropping obstacle groups, and they were significantly correlated with ramie agronomic traits and physiological indicators. This provided important insights into the mechanisms affecting continuous ramie cropping. Accordingly, it is expected that the increase or decrease of sinapic acid, jasmonic acid, glutamine, and inositol in the soil will alleviate obstacles to continuous ramie cropping and promote the healthy development of the ramie industry in the future.